(untitled) (Journal of the College of Basic Education, 2022)
Islamic cities are similar in planning and composition and it was difficult to differentiate between them. Several factors combined that led to its emergence and prosperity, including the religious, military, economic and natural factor. The current city of Samarra played an important role in its emergence and expansion. The city arose and developed on the banks of the Tigris River with its palaces, temples and streets. It is still proud of the presence of the holy shrine (the shrines of the two imams Ali al-Hadi and al-Hasan al-Askari ). And the presence of monuments and prominent cultural landmarks (such as the Great Mosque, Al-Malawiya, and the Principality Palace).